GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG PEMBERIAN ASI EKSKLUSIF PADA BAYI 0-6 BULAN - Syuhada, Wa Ode Nur; Jamuddin, Jamuddin; Adfin, Asrariyah Nur (Jurnal Riset Multidisiplin Agrisosco, 2024)
This research is important because exclusive breastfeeding for the first six months is crucial for infant growth. Although recommended by the WHO, the coverage of exclusive breastfeeding remains low in some areas, possibly due to a lack of maternal knowledge about its benefits. This study aims to understand mothers' knowledge levels, support government programs to promote exclusive breastfeeding and contribute to efforts to reduce infant morbidity and mortality rates World Health Organization (WHO). This study aims to determine the level of maternal knowledge about exclusive breastfeeding for infants aged 0-6 months in the Working Area of UPTD Puskesmas Bukit Kangka, Siompu District, South Buton Regency. This research utilizes a quantitative approach with a descriptive design. The population for this study consists of mothers practicing exclusive breastfeeding with infants aged 0-6 months in the area, totaling 35 individuals. Sampling was conducted using total sampling. For future research, it is recommended to use mixed methods (quantitative and qualitative) to understand social factors affecting maternal knowledge. Additionally, expanding the study area and including variables such as education and employment could provide a broader perspective. Longitudinal studies are also suggested to assess the impact of education on the success of exclusive breastfeeding